The Effect of Implementing Total Quality Management (TQM) on Improving The Reputation of Star Hotels - Lativah, Evi (Politeknik Siber Cerdika Internasional, 2025)
This study aims to examine the effect of Total Quality Management (TQM) implementation on improving the reputation of star-rated hotels in Indonesia. This study uses a quantitative approach with a survey design and cross-sectional approach, which collects data through questionnaires given to hotel managers, service staff, and customers from 100 star-rated hotels in several major cities in Indonesia. The data obtained were analyzed using descriptive statistics, t-test, ANOVA, and linear regression to examine the influence of TQM dimensions on hotel reputation. The results showed that the dimensions of customer focus and continuous improvement have a significant influence on the reputation of star hotels. In addition, the dimensions of quality measurement and employee involvement also have a positive impact, although smaller. These findings indicate that hotels that implement TQM with a focus on service quality and continuous improvement tend to have a better reputation in the eyes of customers. This study provides practical implications for hotel managers to improve customer experience through more systematic and continuous implementation of TQM. In addition, this study contributes to enriching the literature related to the relationship between quality management and hotel reputation.